Visualisation of Bluetongue Virus in the Salivary Apparatus of Culicoides Biting Midges Highlights the Accessory Glands as a Primary Arboviral Infection Site - Marc Guimerà Busquets; Faye V. Brown; Simon T. Carpenter; Karin E. Darpel; Christopher J. Sanders (Biological Procedures Online, 2023)
Abstract Background Arthropods transmit a wide range of pathogens of importance for the global health of humans, animals, and plants. One group of these arthropod vectors, Culicoides biting midges (Diptera: Ceratopogonidae), is the biological vector of several human and animal pathogens, including economically important livestock viruses like bluetongue virus (BTV). Like other arthropod-borne viruses (arboviruses), Culicoides-borne viruses must reach and replicate in the salivary apparatus, from where they can be transmitted to susceptible hosts through the saliva during subsequent blood feeding. Despite the importance of the salivary gland apparatus for pathogen transmission to susceptible animals from the bite of infected Culicoides, these structures have received relatively little attention, perhaps due to the small size and fragility of these vectors. Results In this study, we developed techniques to visualize the infection of the salivary glands and other soft tissues with BTV, in some of the smallest known arbovirus vectors, Culicoides biting midges, using three-dimensional immunofluorescence confocal microscopy. We showed BTV infection of specific structures of the salivary gland apparatus of female Culicoides vectors following oral virus uptake, related visualisation of viral infection in the salivary apparatus to high viral RNA copies in the body, and demonstrated for the first time, that the accessory glands are a primary site for BTV replication within the salivary apparatus. Conclusions Our work has revealed a novel site of virus-vector interactions, and a novel role of the accessory glands of Culicoides in arbovirus amplification and transmission. Our approach would also be applicable to a wide range of arbovirus vector groups including sand flies (Diptera: Psychodidae), as well as provide a powerful tool to investigate arbovirus infection and dissemination, particularly where there are practical challenges in the visualization of small size and delicate tissues of arthropods.